2020
DOI: 10.1002/jbt.22493
|View full text |Cite
|
Sign up to set email alerts
|

Bilobalide assuages morphine‐induced addiction in hippocampal neuron cells through upregulation of microRNA‐101

Abstract: Bilobalide exhibits many biological activities, but its effects on morphine stimulation have not been elucidated. The research aims to explore the function and underlying mechanisms of bilobalide in morphine‐led hippocampal neuron cells. Cells were treated with or without morphine or oxaliplatin (OXA), bilobalide, or SCH772984 dilutions. miR‐101 inhibitor and negative control were transfected into cells. Western blot and quantitative reverse transcription‐polymerase chain reaction were, respectively, conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…BB (Fig. 7), which is a sesquiterpene trilactone extracted from the Ginkgo biloba leaf, has been indicated to exhibit multiple pharmacological effects (41)(42)(43), and it has been investigated as a therapeutic agent for cardiovascular diseases (44), neurological disorders (41,45), ethanol-induced gastric ulcer (46) and cuprizone-induced demyelination (47). Previous studies also demonstrated that BB exerts anti-inflammatory effects (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…BB (Fig. 7), which is a sesquiterpene trilactone extracted from the Ginkgo biloba leaf, has been indicated to exhibit multiple pharmacological effects (41)(42)(43), and it has been investigated as a therapeutic agent for cardiovascular diseases (44), neurological disorders (41,45), ethanol-induced gastric ulcer (46) and cuprizone-induced demyelination (47). Previous studies also demonstrated that BB exerts anti-inflammatory effects (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…The skeleton of 202 was almos same as compound 201, except for one more carbon in a CH3CH2C = O group. These compounds (199)(200)(201)(202) did not exhibit any anti-fungal activities against Gaeumannom graminis, Fusarium moniliforme, Verticillium cinnabarium, and Phyricularia oryzae, nor anti-bacterial activity against Pseudomonas solanacearum, S. aureus, and Salmonella ty murium at 100 μg/disk. Neither of them (199)(200)(201)(202) showed any nematicidal activ against Panagrellus redivivus and Caenorhabditis elegans [153].…”
Section: H Oh O Ohmentioning
confidence: 91%
“…For example, as an antioxidant, bilobalide (140) affects cerebral ischemia injury by activating the Akt/Nrf2 pathway [199]. Furthermore, Bilobalide (140) alleviated morphine-induced addiction in hippocampal neuron cells through the up-regulation of microRNA-101 [200]. In addition, bilobalide (140) inhibited 3T3-L1 preadipocyte differentiation and intracellular lipid accumulation [176] and protects ischemia/reperfusion-induced oxidative stress and inflammatory responses via the MAPK/NF-B pathways [201].…”
Section: Pestalotiopsis Uvicolamentioning
confidence: 99%
See 1 more Smart Citation
“…BB exerts a neuroprotective activity through their non‐competitive inhibition. Besides, BB can be utilized to treat autoimmune encephalomyelitis (Miao et al, 2020), demyelination (Sui et al, 2019), and alleviate hippocampal neuronal cell morphine addiction (Zhang & Zhai, 2020) and other diseases. Based on the above research, BB can not only effectively antagonize cerebral ischemia and ischemia–reperfusion injury, but is also a preferred drug for the treatment of AD and PD.…”
Section: Pharmacological Effects Of Bbmentioning
confidence: 99%